Burns in the middle belt of Ghana: A systematic review - Jonathan Bayuo; Frank Bediako Agyei; Prince Kyei Baffour (Elsevier, 2018)
Background: Burns are a major global public health issue affecting persons of all ages. Various studies have indicated that developing countries share a greater burden of the injury. Despite this fact, Ghana as a developing country lacks a burn repository and that makes it difficult to clearly understand the bigger picture of the injury. To this end, this study aimed to systematically review primary studies of burn occurrence in the country. Methodology: A comprehensive literature search was undertaken using PubMed, ScienceDirect, Google Scholar, MEDLINE and EMBASE. The keywords used were "burns, epidemiology, Ghana, injury, flame burn, scald burn, electric burn, chemical burn, contact burn and explosion". Additional articles were identified by reviewing reference lists. The local journals such as the Postgraduate Medical Journal of Ghana were searched for the articles not indexed in PubMed or EMBASE. MOOSE guidelines were followed in executing this review. At the end of the selection process, seven papers remained and included in the study. Findings: Findings from this review identified that more males than females were involved in burn injuries. Persons within the paediatric age group (particularly those under 10 years of age) were particularly susceptible to burns. This notwithstanding it was noted that there is an increasing occurrence of burns among persons in the working class group (15 years-59 years). Scald was the most common injury among the paediatric age group whilst flame burn was most common among the adult population. The home was noted to be the commonest place for burn occurrence though some disasters at fuel filling stations were recorded. The occurrence of burn was associated with various burned surface area and from the studies reviewed it was noted that higher total burned surface area (TBSA) may be linked to increasing mortality rates. Length of hospitalisation ranged from less than 10 days to 760 days. Epilepsy was reported by one study as a pre-morbid condition. Conclusion: Burns represent a significant public health problem in Ghana and there is a need for the design of more effective intervention to reduce the occurrence of the injury. A larger scale research is imperative to investigate burns epidemiology from a national perspective. Keywords: Burns, Middle belt of Ghana, Epidemiology, Systematic review